(Don't) blame it on the weather: the impact of weather on cruise tourism service quality perception and satisfaction. Issue 4 (2nd October 2018) - Radic, Aleksandar; Lück, Michael
ABSTRACT: Millions of passengers choose to cruise every year, and weather conditions may be a factor that could influence service delivery and consumer satisfaction. This paper empirically examines the impact of (un)favourable weather conditions on perceptions of service quality and overall satisfaction amongst cruise passengers. This quantitative study was conducted with 257 respondents who cruised during favourable and unfavourable weather conditions in the Caribbean. Partial least square path modelling analysis was used to examine the direct impact of (un)favourable weather conditions on service quality and overall satisfaction. The results obtained show that weather perception have a positive impact on perceived service quality.